1980
DOI: 10.1099/0022-1317-46-2-467
|View full text |Cite
|
Sign up to set email alerts
|

Fusion and Haemolysis of Erythrocytes caused by Three Togaviruses: Semliki Forest, Sindbis and Rubella

Abstract: SUMMARYSemliki Forest, Sindbis and rubella viruses can fuse erythrocytes from several different species. Large fusion vesicles consisting of tens to hundreds of red blood cells were seen under optimal conditions. For the haemagglutination and cell fusion to occur the adsorption of virus and further incubation had to be carried out at pH 5"8. Haemagglutination took place over a wide temperature range (o to 4o °C) whereas fusion required temperatures between 37 and 42 °C. Haemolysis of red blood cells induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…This is closely related to the observation of hemolysis and fusion in acid (pH '6.0) by togaviruses such as Semliki forest, Sindbis, and rubella (2,3). Fusion of Semliki forest virus with lipid liposomes in acid has also been observed (4,5).…”
supporting
confidence: 54%
“…This is closely related to the observation of hemolysis and fusion in acid (pH '6.0) by togaviruses such as Semliki forest, Sindbis, and rubella (2,3). Fusion of Semliki forest virus with lipid liposomes in acid has also been observed (4,5).…”
supporting
confidence: 54%
“…It should be noted, however, that virus exposed to acid or neutral pH did cause some hemolysis; A readings from control erythrocyte samples without virus were subtracted from the values obtained with virus. Thus, unlike Semliki Forest virus and influenza virus, which hemolyze well only at acidic pH (18)(19)(20), Sendai virus is active over a pH range from 5 to 9, and shows no significant difference in hemolysis between pH 5 and 7. The hemagglutinating titer per unit of viral protein was determined for each virus preparation after exposure to different pHs, and no difference in hemagglutinating activity was found (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…The ability of Sindbis virus glycoprotein to induce cell-cell fusion after brief exposure to acid pH has been well characterized (30,49). In BHK cells, it has been shown that this process is a two-step event requiring exposure to pH 5.3 followed by a return to pH 7.2 for optimal fusion to be observed (15,30,37).…”
mentioning
confidence: 99%